2014
DOI: 10.1039/c3sm52342j
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the adhesive geometry of neurons: length and polarity control

Abstract: Neurons acquire their functional and morphological axo-dendritic polarity by extending, from competing minor processes (neurites), one long axon among numerous dendrites. We employed complementary sets of micropatterns built from 2 and 6 μm wide stripes of various lengths to constrain hippocampal neuron shapes. Using these geometries, we have (i) limited the number of neuronal extensions to obtain a minimal in vitro system of bipolar neurons and (ii) controlled the neurite width during growth by the generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…In a previous study, we have shown that the control of the neurite width using micropatterns of adhesion yielded a fine tuning of both the length of neurites and the localization of axonal specification (Tomba et al, 2014). To consider the role of actin waves in neuronal growth, in the present work we have used predetermined neuronal morphologies to get new insight into the geometrical determinants of the actin wave dynamics, including temporal periodicity and induced neurite growth.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we have shown that the control of the neurite width using micropatterns of adhesion yielded a fine tuning of both the length of neurites and the localization of axonal specification (Tomba et al, 2014). To consider the role of actin waves in neuronal growth, in the present work we have used predetermined neuronal morphologies to get new insight into the geometrical determinants of the actin wave dynamics, including temporal periodicity and induced neurite growth.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate positioning of cells can lead to the creation of spatially dependant cell-containing devices to promote the advancement of tissue engineered constructs and the creation of fine neuronal networks (Schwarz et al 2014;Tomba et al 2014). This can also help with the understanding of how cells behave in relation to the topography of the substrate (Discher et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Motivations to model the growth cone cover formation of the extracellular gradient that the growth cone senses427273, axonal pathfinding by the gradient cone74757677787980, the growth cone movement in three-dimensional space25818283, axonal specification during neuronal polarization8485868788 and the gradient sensing based on intracellular reaction23257489 or on Bayesian information approach9091.…”
Section: Discussionmentioning
confidence: 99%